Let P ( n ) be a 5th degree polynomial satisfying P ( n ) = n for n = 3 , 4 , 5 , 6 , 7 and P ( 8 ) = 6 4 .
Find P ( 1 2 3 ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
May I ask, how did you (immediately) get 7/15 in P(x) = .... ?
I understand how to properly solve this question using interpolation and method of differences, but I don't know how you managed to pull this off in a single line. Can you share how this feat is (so easily) done? Thanks again!
Log in to reply
We want P ( x ) − x to have zeros at 3 , 4 , 5 , 6 , 7 , so (since P is of degree 5 ) it must be a scalar multiple of ( x − 3 ) ( x − 4 ) ( x − 5 ) ( x − 6 ) ( x − 7 ) . The coefficient 1 5 7 = 5 ! 5 6 is what it takes to have P ( 8 ) = 6 4 .
Log in to reply
Reducing it to a combinatorial part is the best part of your solution
As P ( n ) is a 5th degree polynomial, P ( n ) − n is also a 5th degree polynomial.
P ( n ) − n has roots n = 3 , 4 , 5 , 6 , 7 . So it can be written as P ( n ) − n = k ( n − 3 ) ( n − 4 ) ( n − 5 ) ( n − 6 ) ( n − 7 )
To find value of k , We have been given P ( 8 ) = 6 4
6 4 − 8 = k ( 5 ) ( 4 ) ( 3 ) ( 2 ) ( 1 )
k = 1 5 7
Now
P ( 1 2 3 ) − 1 2 3 = ( 1 2 0 ) ( 1 1 9 ) ( 1 1 8 ) ( 1 1 7 ) ( 1 1 6 ) ∗ 1 5 7
Thus we have P ( 1 2 3 ) = 1 2 3 + 2 2 8 6 9 3 6 2 8 8 0 ∗ 1 5 7 = 1 2 3 + 1 0 6 7 2 3 6 9 3 4 4 = 1 0 6 7 2 3 6 9 4 6 7
Polynomial p ( n ) is of the form:
P ( n ) P ( 8 ) ⟹ P ( n ) P ( 1 2 3 ) = A ( n − 3 ) ( n − 4 ) ( n − 5 ) ( n − 6 ) ( n − 7 ) + n = A ( 5 ) ( 4 ) ( 3 ) ( 2 ) ( 1 ) + 8 = 6 4 = 5 3 ( n − 3 ) ( n − 4 ) ( n − 5 ) ( n − 6 ) ( n − 7 ) − n = 1 5 7 × 1 2 0 × 1 1 9 × 1 1 8 × 1 1 7 × 1 1 6 + 1 2 3 = 1 0 6 7 2 3 6 9 4 6 7 where A is a constant. ⟹ A = 1 5 7
Problem Loading...
Note Loading...
Set Loading...
The required polynomial is P ( x ) = x + 1 5 7 ( x − 3 ) ( x − 4 ) ( x − 5 ) ( x − 6 ) ( x − 7 ) = x + 5 6 ( 5 x − 3 ) making the answer 1 2 3 + 5 6 ( 5 1 2 0 ) = 1 0 6 7 2 3 6 9 4 6 7 .